Electronic health records in nursing from 2000 to 2020: A bibliometric analysis - Ze Luan; Zhiru Zhang; Yanan Gao; Shiyuan Du; Nan Wu; Yulu Chen; Xin Peng (Frontiers Media S.A., 2023)
BackgroundElectronic health records (EHR) is the longitudinal data generated by patients in medical institutions and recorded by electronic medical information systems in the form of digital, which is also the most widespread application of big data in medicine. The purpose of this study was to explore the application of electronic health records in the field of nursing and determine the current research status and hotspots.MethodsA bibliometric analysis of electronic health records in nursing was undertaken from 2000 to 2020. The literature comes from Web of Science Core Collection database. We used CiteSpace (version 5.7 R5; Drexel University), which is a Java-based software that especially visualized collaborative networks and research topics.ResultsA total of 2616 publications were included in the study. We found that publications increased year by year. The Journal of American Medical Informatics Association (n = 921) is the most cited. The United States (n = 1,738) has the most publications in this field. University Penn (n = 63) is the institution with the most publications. There is no influential cooperation network among the authors, of which Bates, David W (n = 12) have the largest number of publications. The relevant publications also focus on the fields of health care science and services, and medical informatics. In keywords, EHR, long-term care, mobile application, inpatient falls, and advance care planning has been researching hotspots in recent years.ConclusionWith the popularization of information systems, the publications of EHR in the nursing field have increased year by year. This study provides the basic structure, potential cooperation, and research trends of EHR in the field of nursing from 2000 to 2020, and provides a reference for nurses to effectively use EHR to help clinical work or scientific researchers explore the potential significances of EHR.